Method for selectively leaching lithium in battery cathode material

By using a combination of wood vinegar and hydrogen peroxide, lithium ions can be selectively recovered from waste lithium iron phosphate batteries, solving the problems of low lithium leaching rate and severe impurity leaching in existing technologies, and realizing a highly efficient and environmentally friendly lithium recycling process.

CN120943274APending Publication Date: 2025-11-14MING CHI UNIVERSITY OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511108705.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-07-18
Filing Date
2025-08-08
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing technologies for recovering lithium from waste lithium iron phosphate batteries suffer from low lithium leaching rates and the leaching of large amounts of impurity metals. Furthermore, the use of strong acids or acetic acid for treatment leads to environmental pollution and increased costs.

Method used

Using wood vinegar as the leaching agent and hydrogen peroxide as the oxidant, lithium ions are selectively recovered and the leaching of impurities such as Al, Fe, and P is inhibited through steps of leaching, filtration, concentration, pH adjustment, centrifugation, precipitation, and drying.

Benefits of technology

It achieves a lithium extraction rate of over 96%, significantly suppresses the leaching of impurities, reduces production costs and environmental impact, and the process is simple and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120943274A_ABST
    Figure CN120943274A_ABST
Patent Text Reader

Abstract

The invention provides a method for selectively leaching lithium in a battery positive electrode material, which comprises the following steps: a leaching step: dipping positive electrode powder of a waste lithium battery in a treatment solution containing a leaching agent and an oxidizing agent, and selectively leaching lithium ions, the leaching agent being wood vinegar; a filtering step: filtering the leaching liquid; a concentration step: concentrating the filtrate to obtain a concentrated solution; a pH adjustment step of adjusting the pH value of the concentrated solution to 7-8 so as to form a precipitate from ions containing at least one element selected from the group consisting of aluminum, iron and phosphorus; a centrifugation step: centrifuging the concentrated solution, and removing the precipitate to obtain a supernatant; a precipitation step: adding carbonate into the supernatant to obtain a mixture containing Li2CO3; a rinsing step: rinsing the mixture; and a drying step: drying the moistened and washed mixture to obtain purified Li2CO3 powder with the industrial grade or above. The invention provides a method for leaching lithium ions from a waste lithium battery by using acid, which realizes high lithium leaching rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a method for selectively leaching lithium from battery cathode materials, particularly a method for leaching lithium ions from waste lithium iron phosphate batteries to prepare high-purity lithium carbonate. Background Technology

[0002] In recent years, the demand for electric vehicles (EVs) and portable electronic products has been increasing. Lithium-ion batteries (LIBs) have become the main energy storage technology due to their lack of memory effect, long lifespan, high energy density, high voltage, and wide operating temperature range. Lithium iron phosphate (LiFePO4) batteries are widely studied due to their robust discharge platform (3.4V), high discharge capacity (170mAh / g), good cycle stability and thermal stability, low raw material cost, environmental friendliness, and abundant raw material sources.

[0003] However, with the increasing demand for lithium iron phosphate batteries, the depletion of natural metal resources (especially lithium) has gradually emerged. On the other hand, if discarded batteries cannot be reused, they will cause serious environmental pollution. Therefore, recovering valuable metals such as lithium from batteries has become an important issue of concern.

[0004] Currently, existing methods for treating waste lithium iron phosphate batteries include wet metallurgy. Wet metallurgy primarily uses strong inorganic acids (such as hydrochloric acid and sulfuric acid) as the treatment solution to leach lithium ions from the waste batteries, followed by precipitation for recovery. However, the treatment of waste liquid requires the use of large amounts of alkaline solution to neutralize the strong inorganic acids, significantly increasing treatment costs. Furthermore, the leaching process generates large amounts of toxic and irritating gases, making it quite environmentally unfriendly.

[0005] Furthermore, although existing technologies (Table 1 below) have confirmed that using weak acids such as acetic acid or lemon juice for leaching, combined with an appropriate reducing agent (e.g., H₂O₂), can achieve lithium leaching efficiency of over 90%, it also dissolves a large amount of impurity metals (e.g., Al, Fe, P). Moreover, acetic acid, as an industrial chemical, has high production costs, and its synthesis process may generate greenhouse gases such as carbon dioxide and carbon monoxide, which have adverse environmental impacts.

[0006] Table 1: Metals extracted from spent lithium iron phosphate batteries using acid leaching

[0007]

[0008]

[0009] Therefore, it is necessary to develop a more environmentally friendly acid as a leaching agent that can not only achieve a high lithium extraction rate but also effectively suppress the leaching of impurities such as Al, Fe, and P. Summary of the Invention

[0010] In view of this, the purpose of this invention is to develop a method for selectively leaching lithium from battery cathode materials, using wood vinegar, which is available in nature, as the leaching agent. This method not only conforms to the concept of green chemistry, but also achieves a lithium leaching rate of over 96%, while suppressing the leaching of impurities such as Al, Fe, and P.

[0011] In view of the problems encountered by the prior art, the present invention aims to provide a method for selectively leaching lithium from a battery cathode material, comprising:

[0012] The leaching step involves immersing the positive electrode powder of the waste lithium battery in a treatment solution containing a leaching agent and an oxidant to selectively leach out lithium ions, wherein the leaching agent is wood vinegar.

[0013] The filtration step involves filtering the leachate containing the lithium ions to remove solids.

[0014] The concentration step involves concentrating the filtrate obtained from the filtration step to remove water and increase the lithium ion concentration to 20 g / L to 60 g / L, resulting in a lithium-ion-rich concentrate.

[0015] The pH adjustment step adjusts the pH of the lithium-ion-rich concentrate to 7 to 8 so that ions containing at least one of the elements aluminum, iron, and phosphorus form a precipitate.

[0016] The centrifugation step involves centrifuging the concentrate obtained after the pH adjustment step to remove the precipitate and obtain the supernatant.

[0017] In the precipitation step, a saturated carbonate solution is added to the supernatant obtained after the centrifugation step to obtain a mixture containing Li2CO3.

[0018] The rinsing step involves rinsing the mixture obtained through the precipitation step with water; and

[0019] The drying step involves drying the rinsed mixture to obtain purified Li2CO3 powder of industrial grade or higher.

[0020] In one embodiment of the present invention, the waste lithium battery may be a waste lithium iron phosphate battery, and the solid may contain iron phosphate.

[0021] In one embodiment of the present invention, the oxidant may be hydrogen peroxide.

[0022] In one embodiment of the present invention, the treatment solution can be prepared by adding hydrogen peroxide to a wood vinegar solution to make the concentration of hydrogen peroxide in the treatment solution 2 vol% to 16 vol%, wherein the wood vinegar solution may include 2 to 20 wt% acetic acid.

[0023] In one embodiment of the present invention, the impregnation in the leaching step can be carried out at room temperature and the impregnation time can be between 10 minutes and 240 minutes.

[0024] In one embodiment of the present invention, in the leaching step, the solid-liquid ratio of the positive electrode powder to the treatment liquid can be from 10 g / L to 60 g / L.

[0025] In one embodiment of the invention, the carbonate may be selected from at least one of the group consisting of sodium carbonate, sodium bicarbonate, and potassium bicarbonate.

[0026] In one embodiment of the present invention, the carbonate may be selected from a derivative of the carbonate ion.

[0027] In one embodiment of the present invention, the carbonate may be selected from sodium carbonate, and in the precipitation step, the saturated carbonate solution may be added to the supernatant at a rate of 1 to 5 mL / min for 1 to 3 hours, while stirring at a speed of 200 to 300 rpm and maintaining the supernatant at 90°C to 95°C.

[0028] In one embodiment of the invention, the washed mixture may be dried in a vacuum oven for 10 to 14 hours during the drying step.

[0029] In one embodiment of the present invention, the lithium extraction rate of the leaching step is above 95%.

[0030] The advantages of this invention are as follows: First, by using wood vinegar as a leaching agent, it is possible to achieve efficient leaching of lithium in lithium battery cathode materials, while effectively inhibiting the dissolution of impurities such as Al, Fe, and P, thereby improving the purity of the recovered Li2CO3 powder; Second, the reaction conditions are mild and the process is simple, which can reduce the need for excessive use of reagents and reduce energy consumption; Third, wood vinegar is derived from waste products in the carbonization process of wood or plants, which is a natural and abundant resource that can replace industrial acetic acid, reduce production costs, and reduce environmental impact.

[0031] The effects of this invention are not limited to those described above, and other effects not mentioned will be clearly understood by those skilled in the art from the description of the claims. Attached Figure Description

[0032] The above and other aspects, features and advantages of the invention will become clearer from the following detailed description taken in conjunction with the accompanying drawings, wherein:

[0033] Figure 1 This is a flowchart of the method for selectively leaching lithium from the positive electrode material of a battery according to the present invention;

[0034] Figure 2 The XRD patterns of the lithium iron phosphate battery cathode powder used in this invention and the reference powder are shown.

[0035] Figure 3 XRD patterns of lithium carbonate powder recovered according to the method of the present invention and a reference powder; and

[0036] Figure 4 SEM image of lithium carbonate powder recovered according to the method of the present invention.

[0037] Explanation of reference numerals in the attached figures:

[0038] S10: Extraction step;

[0039] S20: Filtration step;

[0040] S30: Concentration step;

[0041] S40: pH adjustment steps;

[0042] S50: Centrifugation step;

[0043] S60: Precipitation step;

[0044] S70: Rinsing / washing steps;

[0045] S80: Drying step. Detailed Implementation

[0046] The advantages and features of the present invention and its implementation methods will become clearer from the embodiments described below. However, the present invention is not limited to the embodiments described below, but can be implemented in various different forms.

[0047] Without causing contradictions, any technical feature in any aspect of the present invention may be combined with other aspects of the present invention.

[0048] On the other hand, wood vinegar (Pyroligneous Acid) is a waste product generated during the carbonization of wood or plants, producing approximately 6,000 to 7,000 kilograms annually. It serves as an important source of organic acids (such as acetic acid). Compared to industrially produced acetic acid, wood vinegar is a naturally occurring waste product, and its abundant availability effectively reduces production costs.

[0049] However, there is currently no technology that uses wood vinegar as a leaching agent to extract lithium from battery cathode materials.

[0050] Therefore, refer to Figure 1 The method for selectively leaching lithium from battery cathode materials according to the present invention includes: leaching step S10, filtration step S20, concentration step S30, pH adjustment step S40, centrifugation step S50, precipitation step S60, rinsing step S70, and drying step S80.

[0051] First, in the leaching step S10, the positive electrode powder of the waste lithium battery is immersed in a treatment solution containing a leaching agent and an oxidant to selectively leach out lithium ions, wherein the leaching agent is wood vinegar.

[0052] In one embodiment, the waste lithium battery can be a waste lithium iron phosphate (LiFePO4) battery, in which case the solid remaining after the positive electrode powder has leached out lithium ions may contain iron phosphate.

[0053] Before performing the leaching step S10, the elements in the waste LiFePO4 battery cathode powder can be determined using inductively coupled plasma (ICP). As confirmed in Table 2 below, the waste LiFePO4 battery cathode powder used in this invention contains 3.38 wt% Li and 26.24 wt% Fe.

[0054] Table 2: Composition of the positive electrode powder

[0055]

[0056] ICP may include at least one of inductively coupled plasma mass spectrometry (ICP-MS) and inductively coupled plasma optical emission spectrometry (ICP-OES).

[0057] Furthermore, in addition to elemental analysis, XRD analysis can also be performed on the cathode powder from waste LiFePO4 batteries. Figure 2 The XRD results obtained by 2θ scanning in the range of 10 to 90 degrees are shown, and compared with the diffraction peaks of the reference sample. Here, COD (Crystallography Open Database) is an open database of crystal structures, providing crystal structure data for hundreds of thousands of small molecules.

[0058] The XRD results show that all peaks of the LiFePO4 powder are consistent with all reference peaks of the reference sample powder (COD: 96-210-0917), indicating that the crystal structure of the powder is consistent with the standard LiFePO4 crystal structure, thus confirming that the LiFePO4 powder used in this invention has high purity.

[0059] In one embodiment, the wood vinegar may include 2 to 20 wt%, preferably 5 to 10 wt%, of acetic acid (CH3COOH).

[0060] Wood vinegar, also known as pyruvic acid, is a dark-colored acidic liquid produced through the decomposition and distillation process of wood or plants. It contains 80 to 90 wt% water and 10 to 20 wt% organic compounds, including acetic acid, phenols, acids, alcohols, aldehydes, and trace amounts of calcium. Acetic acid accounts for approximately 50 wt% of the organic compounds, making it one of the most abundant organic acids in wood vinegar.

[0061] In this invention, by using wood vinegar as a leaching agent to selectively leach waste LiFePO4 battery cathode powder, lithium can be efficiently leached at room temperature or normal pressure, which can reduce the energy input required for heating or pressurization.

[0062] In one embodiment, the oxidant may be hydrogen peroxide.

[0063] When the oxidant is hydrogen peroxide and the waste lithium battery is a waste lithium iron phosphate (LiFePO4) battery, the following reaction is carried out in the leaching step S10 to selectively leach lithium ions:

[0064] H2O2 + 2H + + 2e - → H2O (1)

[0065] CH3COOH (aq) → CH3COO - (aq) + H + (aq), pK a = 4.75 (2) LiFePO4(II)(s)+CH3COOH(aq)+1 / 2H2O2

[0066] → FePO4 (III) (s) + CH3COO - (aq) + Li + + H2O (l) (3)

[0067] Li + The reaction mechanism of leaching from LiFePO4 is as follows: the crystal structure of LiFePO4 is mainly composed of Li + Fe 2+ and PO4 3- It has a stable olivine structure. When an oxidizing agent provides oxidizing power, ferrous ions (Fe2+) are oxidized. 2+ It is oxidized to ferric ions (Fe3+) 3+ When ), the lattice stability decreases, and after the lattice stability decreases, Li + It is easier for it to dissociate from its lattice position and be further released into the processing liquid.

[0068] Among them, Fe2+ Oxidized to Fe 3+ The purpose is Fe 3+ It is more likely to form precipitates, such as iron phosphate (FePO4(III)), and thus will not be leached.

[0069] In one embodiment, the treatment solution can be prepared by adding hydrogen peroxide to wood vinegar (e.g., pure wood vinegar) to achieve a hydrogen peroxide concentration of 2 vol% to 16 vol%, such as 2 vol%, 9 vol%, 16 vol%, preferably 14 vol%.

[0070] In one embodiment, in the leaching step S10, the impregnation can be carried out at room temperature, and the impregnation time can be between 10 minutes and 240 minutes, for example 10 minutes, 125 minutes, 240 minutes, preferably 210 minutes.

[0071] During the impregnation process, the chemical reaction between the positive electrode powder and the treatment solution consumes some of the acid, causing the pH value of the solution to rise, for example, from 2.78 to 4.21.

[0072] In the leaching step S10, the solid-liquid ratio of the positive electrode powder to the treatment liquid can be from 10 g / L to 60 g / L, for example, 10 g / L, 35 g / L, 60 g / L, preferably 30 g / L.

[0073] In this paper, the solid-to-liquid ratio (S / L ratio) is expressed as the ratio of the solid to be leached to the treatment liquid. For example, in the leaching step S10, a solid-to-liquid ratio of 30 g / L is set, which means that 30 g of LiFePO4 powder is treated with 1 liter of treatment liquid.

[0074] An appropriate solid-liquid ratio has a crucial impact on leaching efficiency. For example, if there is too much solid, the treatment solution may not be sufficient to fully dissociate the lithium metal, resulting in incomplete leaching; while if there is too much treatment solution, it may reduce the concentration of the leached product in the solution, increasing the cost and difficulty of subsequent concentration or separation, and also wasting the treatment solution.

[0075] Subsequently, in filtration step S20, the leaching solution containing lithium ions is filtered to remove solids (such as FePO4). After completion, the lithium leaching rate can be measured. The measurement method is to analyze the elemental content in the leaching solution using ICP / OES (as in subsequent centrifugation step S50).

[0076] Subsequently, in the concentration step S30, the filtrate obtained after the filtration step S20 is concentrated to remove water and increase the lithium ion concentration to 20 g / L to 60 g / L, for example 20 g / L, 50 g / L, 60 g / L, preferably 40 g / L.

[0077] After the concentration step S30 is completed, a lithium-ion-rich product (Li) is obtained. + The solution contains unwanted impurities, such as Al. 3+ Cu 2+ Fe 2+ Fe 3+ PO4 3- Impurity ions, etc.

[0078] Therefore, further effective separation of unwanted impurity ions is needed to recover valuable lithium-containing compounds.

[0079] Therefore, in the subsequent pH adjustment step S40, the pH of the lithium-ion-rich concentrate is adjusted to 7 to 8 so that ions containing at least one of the elements aluminum, iron, and phosphorus form a precipitate.

[0080] In one embodiment, the alkaline solution used to adjust the pH value can be sodium hydroxide, potassium hydroxide, or ammonia, preferably sodium hydroxide (4M).

[0081] Add alkali solution (to provide OH-) - After that, OH - The precipitates formed with the aforementioned impurity ions may include at least one of: aluminum hydroxide (Al(OH)3), copper hydroxide (Cu(OH)2), ferrous hydroxide (Fe(OH)2), and ferric hydroxide (Fe(OH)3); while lithium ions (Li... + It remains in a stable dissociated state at pH 7 to 8 and will not form a precipitate.

[0082] In addition, PO4 3- It itself does not react with OH - It can react with metal ions at pH 7 to 8 to form phosphate precipitates, such as FePO4, AlPO4, and Cu3(PO4)2.

[0083] Subsequently, in the centrifugation step S50, the concentrate obtained after the pH adjustment step S40 is centrifuged to remove the above precipitate and obtain the supernatant.

[0084] Under pH conditions of 7 to 8, the aforementioned impurity ions will form precipitates that are insoluble in water, while lithium ions remain in a dissociated state. The precipitates can be separated from the solution by centrifugation. This allows the pH adjustment step S40 and the centrifugation step S50 to effectively remove impurity elements from the solution, thereby purifying the lithium-containing solution.

[0085] After centrifugation step S50 is completed, the elemental composition of the supernatant is analyzed using ICP / OES. The purpose is to determine the content of Li and other elements (such as Al, Fe, and P) in the supernatant to calculate the leaching rate. The formula for calculating the leaching rate is as follows:

[0086]

[0087] The leaching rate was calculated based on the elemental content in the cathode powder (previously measured by ICP, as shown in Table 2) and the actual elemental content in the supernatant measured by ICP / OES.

[0088] For example, the lithium leaching rate (%) = weight of lithium in the supernatant ÷ weight of lithium in the LiFePO4 cathode powder x 100.

[0089] As shown in Table 3, the present invention compared seven different treatment solutions (Comparative Examples 1 to 7) with a Korean wood vinegar solution containing hydrogen peroxide (Example 1). The leaching was performed under the following identical conditions: solid-liquid ratio of 30 g / L; room temperature; reaction time of 60 minutes; and oxidant concentration of 6 vol%.

[0090] Table 3:

[0091]

[0092]

[0093] As shown in the table above, the Li leaching rate of Example 1 is 95.67%, indicating that the lithium leaching rate in leaching step S10 can reach more than 95%, which is significantly higher than the results of using hydrogen peroxide alone or without an oxidant in Comparative Example 1 (16.63%) and Comparative Example 2 (17.26%).

[0094] Furthermore, compared to other acidic leaching agents (such as acetic acid in Comparative Example 3 and sulfuric acid in Comparative Example 6), the wood vinegar of Example 1 still achieved a similar or even higher Li leaching rate, and the effect was stable.

[0095] Moreover, Example 1 also showed a significant inhibitory effect on impurities such as Al, Fe, and P. The leaching rate of Al was only 4.43%, which was much lower than the leaching rate of other acidic leaching agents in the comparative examples (such as Comparative Example 6). Furthermore, the leaching rates of Fe and P were also kept at extremely low values ​​(0.44% and 3.30%, respectively).

[0096] In particular, Example 1 showed the most significant inhibitory effect on Al, because Al 3+ The concentration is significantly reduced, which avoids its reaction with carbonate ions (CO3-) in the subsequent precipitation step S60. 2-The reaction reduces the possibility of aluminum compound precipitation, thus ensuring that the precipitation process of Li2CO3 is not disturbed, further improving the purity of Li2CO3. This demonstrates that the combination of wood vinegar and H2O2 used in this invention has extremely high selective leaching ability.

[0097] Subsequently, in precipitation step S60, a saturated carbonate solution is added to the supernatant obtained after centrifugation step S50 to obtain a mixture containing Li2CO3.

[0098] In one embodiment, the carbonate may be selected from at least one of the group consisting of sodium carbonate, sodium bicarbonate, and potassium bicarbonate, preferably sodium carbonate.

[0099] In one embodiment, the carbonate may be selected from a derivative of the carbonate ion.

[0100] In precipitation step S60, a saturated carbonate solution can be added to the supernatant at a rate of 1 to 5 mL / min for 1 to 3 hours, while stirring at a speed of 200 to 300 rpm and maintaining the supernatant at 90°C to 95°C.

[0101] Preferably, a saturated sodium carbonate solution is added to the supernatant at a rate of 1 to 5 mL / min for 2 hours, while stirring at 300 rpm and maintaining the supernatant at 95°C.

[0102] Subsequently, in the rinsing step S70, the mixture obtained via the precipitation step S60 is rinsed with water.

[0103] In one embodiment, the water used can be ultrapure water or deionized water, preferably boiled ultrapure water, to ensure the purity of the washing process.

[0104] Finally, in the drying step S80, the rinsed mixture is dried to obtain purified industrial-grade or even electronic-grade Li2CO3 powder.

[0105] In one embodiment, in the drying step S80, the rinsed mixture may be dried in a vacuum oven for 10 to 14 hours, for example, 10, 12, or 14 hours, preferably 12 hours.

[0106] Reference Figure 3 As can be seen from the XRD results, all peaks of the Li2CO3 powder (Example 1) recovered by the method according to the present invention are consistent with all reference peaks of the reference sample powder (COD: 96-231-0704), which indicates that the Li2CO3 prepared by the method of the present invention has high purity and confirms the effectiveness of the selective leaching of the present invention.

[0107] Reference Figure 4 SEM results showed that the Li2CO3 powder recovered by the method according to the present invention (Example 1) has good particle morphology, with particle size concentrated in the micron range, which can meet the needs of most industrial applications.

[0108] In summary, the advantages of this invention are as follows: First, using wood vinegar as a leaching agent enables efficient leaching of lithium from lithium battery cathode materials, while effectively inhibiting the dissolution of impurities such as Al, Fe, and P, thereby improving the purity of the recovered Li2CO3 powder; Second, the reaction conditions are mild and the process is simple, reducing the need for excessive reagent use and lowering energy consumption; Third, wood vinegar is derived from waste products during the carbonization of wood or plants, making it a natural and abundant resource that can replace industrial acetic acid, reducing production costs and minimizing environmental impact.

[0109] Those skilled in the art will understand that various modifications and changes can be made to the above embodiments without departing from the basic characteristics of the present invention, such as combining, separating, replacing, and changing the configuration.

[0110] Therefore, the embodiments of the present invention are intended to illustrate the scope of the technical concept of the present invention, but the scope of the present invention is not limited to the above embodiments. Thus, any modifications or changes made to the present invention under the same inventive spirit should still be included within the scope of protection intended by the present invention.

Claims

1. A method for selectively leaching lithium from a battery cathode material, characterized in that, include: The leaching step involves immersing the positive electrode powder of the waste lithium battery in a treatment solution containing a leaching agent and an oxidant to selectively leach out lithium ions, wherein the leaching agent is wood vinegar. The filtration step involves filtering the leachate containing the lithium ions to remove solids. The concentration step involves concentrating the filtrate obtained after the filtration step to remove water and increase the lithium ion concentration to 20 g / L to 60 g / L, thereby obtaining a lithium-ion-rich concentrate. The pH adjustment step adjusts the pH of the lithium-ion-rich concentrate to 7 to 8 so that ions containing at least one of the elements aluminum, iron, and phosphorus form a precipitate. The centrifugation step involves centrifuging the concentrated solution obtained after the pH adjustment step to remove the precipitate and obtain a supernatant. In the precipitation step, a saturated carbonate solution is added to the supernatant obtained after the centrifugation step to obtain a mixture containing Li2CO3. The rinsing step involves rinsing the mixture obtained through the precipitation step with water; and The drying step involves drying the rinsed mixture to obtain purified Li2CO3 powder of industrial grade or higher.

2. The method according to claim 1, characterized in that, The waste lithium battery is a waste lithium iron phosphate battery, the solid contains iron phosphate, and the oxidant is hydrogen peroxide.

3. The method according to claim 2, characterized in that, The treatment solution is prepared by adding hydrogen peroxide to wood vinegar to achieve a hydrogen peroxide concentration of 2 vol% to 16 vol%.

4. The method according to claim 1, characterized in that, In the leaching step, the impregnation is carried out at room temperature and the impregnation time is between 10 minutes and 240 minutes.

5. The method according to claim 1, characterized in that, In the leaching step, the solid-liquid ratio of the positive electrode powder to the treatment solution is 10 g / L to 60 g / L.

6. The method according to claim 1, characterized in that, The carbonate is selected from at least one of the group consisting of sodium carbonate, sodium bicarbonate, and potassium bicarbonate.

7. The method according to claim 1, characterized in that, The carbonate is selected from derivatives of the carbonate ion.

8. The method according to claim 1, characterized in that, The carbonate is selected from sodium carbonate, and In the precipitation step, the saturated carbonate solution is added to the supernatant at a rate of 1 to 5 mL / min for 1 to 3 hours, while stirring at a speed of 200 to 300 rpm and maintaining the supernatant at 90°C to 95°C.

9. The method according to claim 1, characterized in that, In the drying step, the rinsed mixture is dried in a vacuum oven for 10 to 14 hours.

10. The method according to claim 1, characterized in that, The lithium extraction rate in the extraction step is over 95%.